TINDAK UJAR ILOKUSI DALAM FILM FIREPROOF KARYA ALEX KENDRICK SUATU ANALISIS PRAGMATIK - TULANGOW, RENDY MORIS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT Language is the most important of human life. In communication, people do not only utter sentences but also transfer it into behavior and this is called speech act. According to Searle illocutionary act is one part of speech act and it has five categories, those are assertive, directives, commisives, expressives and declaratives. The purpose of this research is to identify, classify and analyze illocutionary act and its function in the film entitled Fireproof by Alex Kendrick. The collected data have been identified of the utterances which contain illocutionary acts that are used by the characters in the film and analyzed descriptively based on the theory of Searle. The finding shows that there are four kinds of illocutionary act in the film, those are assertives, directives, expressives, and commisives whereas declaratives is not found in the utterances that uttered by the characters. The outcome of this study is to give contribution of the language development in linguistic study especially on illocutionary acts through pragmatic study and to be expected to help the students of English Department in understanding illocutionary act in the film. Keywords : Illocutionary Act, Film Fireproof.